Integrative species delimitation in the deep-sea genus Thaumastosoma Hessler, 1970 (Isopoda, Asellota, Nannoniscidae) reveals a new genus and species from the Atlantic and central Pacific abyss. (February 2018) - Kaiser, Stefanie; Brix, Saskia; Kihara, Terue C.; Janssen, Annika; Jennings, Robert M.
Abstract: Combined morphological and molecular analyses provided evidence for a new nannoniscid genu s, Ketosoma gen. nov., including new species from abyssal waters of the equatorial NE Atlantic (eastern Vema Fracture Zone), SW Atlantic (Argentine Basin) as well as equatorial NE Pacific (Clarion Clipperton Fracture Zone, CCZ). Using mitochondrial (COI and 16S) and nuclear (18S) DNA markers together with morphological information from light scanning and confocal laser scanning microscopy we found clear differences between Ketosoma and its putative sister taxon Thaumastosoma Hessler, 1970. The new genus can be distinguished from the latter by the presence of a robust seta on pereonite 1 anterolateral corner and the lack of a ventral spine on the female operculum and pereonite 7 amongst others. Different species delimitation (SD) analyses were performed alongside morphological assessment to delineate species within Ketosoma . Here, four new species are described: Ketosoma vemae gen. et sp. nov. and K. hessleri gen. et sp. nov. from the eastern Vema Fracture Zone, K. werneri gen. et sp. nov. from the Argentine Basin and K. ruehlemanni gen. et sp. nov. from the CCZ. There is morphological and genetic evidence for the presence of at least two further Ketosoma species from the CCZ. Species within Thaumastosoma are reassessed; Thaumastosoma platycarpus Hessler, 1970 and T. tenue Hessler, 1970 are redescribed based on type material and the diagnosis updated accordingly. Furthermore, a new Thaumastosoma species, T. diva sp. nov., is described from the Argentine Basin. Thaumastosoma distinctum (Birstein, 1963) and T. jebamoni (George, 2001) are assigned to Ketosoma, with the latter species regarded as a nomen dubium.